PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL KOOPERATIF TIPE MAKE A MATCH BERBANTUAN WORDWALL DI KELAS V UPT SDN 03 PASAR AMPING PARAK KABUPATEN PESISIR SELATAN - Azura; Yanti Fitria; Atri Waldi; Hana Shilfia Iraqi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to describe the improvement in learning outcomes of Pancasila Education using the Wordwall-Assisted Make a Match Type Cooperative model in class V UPT SDN 03 Pasar Amping Parak, Pesisir Selatan Regency. This research applies a type of Classroom Action Research (PTK) using qualitative and quantitative approaches. The subjects in this research were teachers (researchers) and 20 students consisting of 12 men and 8 women. The results of this research show an increase in: a) open modules in cycle I with an average of 87.5% (Good) and cycle II 95.8% (Very Good), b) implementation in the teacher aspect of cycle I with an average of 82.5% (Good) and cycle II 97.5% (Very Good), while implementation in the student aspect of cycle I with an average of 82.5% (Good) and cycle II 97.5% (Very Good), c) assessment of participants students in improving learning outcomes in cycle I by 74.85% and cycle II with an average of 87.8%. Based on these results, it can be concluded that the make a match type cooperative model assisted by wordwall can improve student learning outcomes in Pancasila Education learning in class V UPT SDN 03 Pasar Amping Parak, Pesisir Selatan Regency.